Hypervascular hepatic mass in a patient with breast cancer - Zheng, Yiling; Li, Zhuo; Wang, Liming; Wu, Fan; Wu, Jianxiong (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Zheng Y, Li Z, Wang L, Wu F, Wu J. Hypervascular hepatic mass in a patient with breast cancer. Turk J Gastroenterol 2020; 31(11): 825-6.